Method for preparing W surface modified graphene nanosheet through molten salt method
The preparation of W surface modified graphene nanosheets by the molten salt method solved the problem of poor bonding between graphene and metal matrix, and achieved the full utilization of graphene's excellent performance in metal-based composite materials, improving the overall performance of composite materials.
Patent Information
- Application Number
- CN202510003435.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-02
AI Technical Summary
When preparing metal-based composite materials, the interface bond between graphene and the matrix is poor, resulting in the inability to fully utilize the excellent properties of graphene, especially in the problems of poor wetting and excessive interface reaction.
W surface modified graphene nanosheets were prepared by molten salt method. By heat treatment of graphene and WO3 particles under an argon atmosphere, the reaction activation energy was reduced by using the molten salt system to achieve reduction and surface modification of W elements.
It effectively improves the interface bonding ability between graphene and metal matrix, inhibits severe interface reactions, and makes full use of the mechanical, thermal and electrical conductivity of graphene, improving the overall performance of composite materials.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing W surface-modified graphene nanosheets by a molten salt method. Background Art
[0002] With the continuous development of modern materials science and technology, the demand for high-performance materials is growing. Metal-based composites have become one of the hot topics in the field of materials research because they combine the toughness of the metal matrix with the special properties of other reinforcement phases. Among them, graphene nanosheets have shown excellent performance due to their unique structure and have attracted much attention in the research and development of high-performance metal-based composites.
[0003] Graphene has significant mechanical performance advantages, and its strength and modulus are in a leading position among many materials. For example, its tensile strength can be as high as about 130GPa, and its Young's modulus is about 1TPa. This excellent mechanical property makes it an ideal candidate material for enhancing the mechanical properties of metal-based composites. At the same time, graphene also performs exceptionally well in thermal and electrical conductivity. Its thermal conductivity can reach several kilowatts / (meter·Kelvin) at room temperature, and its electrical conductivity is close to that of metallic copper, which means that it has the potential to significantly improve the thermal and electrical properties of metal-based composites and expand its application in many fields such as electronics, aerospace, and automobiles.
[0004] However, in the practice of compounding graphene with metal matrix to prepare high-performance metal matrix composites, many technical difficulties have been encountered, among which the most prominent is the interface problem between graphene and matrix. When graphene is compounded with common metal materials such as copper and nickel, poor wettability becomes a key factor restricting interface bonding. From a microscopic point of view, wettability mainly depends on the surface energy of the material. The high interface energy between graphene and metals such as copper makes it difficult for graphene to form a tight bonding interface on the metal surface when the two are in contact. For example, in the traditional composite process, even if graphene and copper powder are simply mixed and pressed and sintered, due to poor wettability, a large number of voids and defects will be formed at the interface, so that the interface bonding between the two relies only on weak physical adsorption force, lacking strong interactions such as chemical bonding. This weak interface bonding mode seriously hinders the effective transmission of graphene mechanical properties. When subjected to external loads, due to the easy occurrence of stress concentration at the interface, graphene cannot give full play to its high strength and high modulus characteristics, and cannot play a good reinforcing role on the metal matrix, resulting in limited improvement in the overall mechanical properties of the composite material. In terms of thermal and electrical conductivity, due to the loose interface bonding, the transmission of electrons and phonons at the interface is greatly hindered, making it difficult for the thermal and electrical conductivity of the composite material to achieve the expected results, and unable to fully utilize the excellent physical properties of graphene.
[0005] On the other hand, when graphene is compounded with metal materials such as titanium, it faces the problem of excessive interface reaction. Titanium is a metal with high chemical activity. Under certain temperature and environmental conditions, it will undergo violent chemical reactions with graphene to generate metal carbides such as TiC. This interfacial reaction essentially changes the structure of graphene. For example, when preparing graphene-reinforced titanium-based composites by high-temperature sintering, as the temperature rises, the interfacial reaction gradually intensifies, the special structure of graphene gradually disintegrates, and the excellent mechanical properties, thermal conductivity and electrical conductivity that it can originally provide also decrease significantly. This situation in which the graphene structure is destroyed due to interfacial reaction also makes it impossible for graphene to effectively play its reinforcing role in titanium-based composites, which seriously limits the performance improvement and application expansion of such metal-based composites.
[0006] The metal surface modified graphene nanosheets prepared at this stage are mainly elements such as Ni and Ag. Although they can improve the interface between graphene and the metal matrix in the composite material to a certain extent, there is still the problem that elements such as Ni and Ag are easy to react with other metals to generate brittle intermetallic compounds, resulting in reduced plasticity of the composite material. The reason why W is selected as the surface modification element is that it can be dissolved in most metals, which can not only ensure the bonding effect of the interface, but also does not cause serious interface reactions with the metal matrix to generate brittle intermetallic compounds. At the same time, the W atoms dissolved in the metal matrix are conducive to improving the high temperature performance of the matrix. At the same time, the methods for surface modification of graphene at this stage are mainly wet modification technologies such as hydrothermal method, which have complex processes, low output and yield, and are not suitable for W elements. Therefore, it is urgent to develop a more efficient W element surface modification process. In summary, in the existing technology for preparing metal-based composite materials, there is a poor interface problem between graphene and the matrix, whether it is poor wettability or excessive interface reaction, which seriously restricts the full utilization of the excellent performance of graphene in metal-based composite materials. It is urgent to develop new technologies and methods to improve the interface bonding condition between graphene and the metal matrix to achieve the preparation of high-performance metal-based composite materials. Summary of the invention
[0007] The present invention aims to solve the problem of poor interface between graphene and matrix in metal matrix composite materials, and provides a method for preparing W surface modified graphene nanosheets by a molten salt method.
[0008] A method for preparing W surface-modified graphene nanosheets by a molten salt method is specifically carried out in the following steps:
[0009] 1. The graphene nanosheets are washed with distilled water and dried, and then ultrasonically dispersed in a hydrofluoric acid solution to functionalize the graphene surface. After the ultrasonic dispersion is completed, the graphene nanosheets are washed with distilled water again and dried to obtain graphene with functionalized surface;
[0010] 2. Mechanically mix NaCl and KCl to obtain mixed salt;
[0011] 3. WO 3 The particles and the graphene with surface functional groups are mechanically mixed uniformly to obtain a mixed powder; the mixed powder is spread on the bottom of a crucible, and the surface of the mixed powder is covered with a mixed salt to obtain a crucible containing the mixed salt and the mixed powder;
[0012] 4. Put the crucible containing the mixed salt and the mixed powder into a heat treatment furnace to perform surface modification of graphene under an argon atmosphere; after the reaction is completed, cool the furnace to below 100° C. under an argon atmosphere and take out the crucible;
[0013] 5. The reactants in the crucible are taken out, rinsed with distilled water and filtered with filter paper, and the graphene surface modified by the W element is separated and dried, thereby completing the preparation of the W element surface modified graphene nanosheets by the molten salt method.
[0014] Beneficial effects of the invention: The method is simple in process and has good surface modification effect, which solves the problem of poor interface between graphene and matrix in metal-based composite materials. Taking titanium-based composite materials as an example, after surface modification, the serious interface reaction between graphene and titanium matrix is effectively suppressed, so that graphene can be retained. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a SEM photo of the W element surface-modified graphene nanosheets prepared in Example;
[0016] Figure 2 for Figure 1 Corresponding W element distribution diagram;
[0017] Figure 3 It is a comparison diagram of engineering stress-strain of pure titanium and W element surface modified graphene nanosheet reinforced Ti-based composite material prepared by the embodiment. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0019] Specific implementation method 1: In this implementation method, a method for preparing W surface-modified graphene nanosheets by a molten salt method is specifically carried out in the following steps:
[0020] 1. The graphene nanosheets are washed with distilled water and dried, and then ultrasonically dispersed in a hydrofluoric acid solution to functionalize the graphene surface. After the ultrasonic dispersion is completed, the graphene nanosheets are washed with distilled water again and dried to obtain graphene with functionalized surface;
[0021] 2. Mechanically mix NaCl and KCl to obtain mixed salt;
[0022] 3. WO 3 The particles and the graphene with surface functional groups are mechanically mixed uniformly to obtain a mixed powder; the mixed powder is spread on the bottom of a crucible, and the surface of the mixed powder is covered with a mixed salt to obtain a crucible containing the mixed salt and the mixed powder;
[0023] 4. Put the crucible containing the mixed salt and the mixed powder into a heat treatment furnace to perform surface modification of graphene under an argon atmosphere; after the reaction is completed, cool the furnace to below 100° C. under an argon atmosphere and take out the crucible;
[0024] 5. The reactants in the crucible are taken out, rinsed with distilled water and filtered with filter paper, and the graphene surface modified by the W element is separated and dried, thereby completing the preparation of the W element surface modified graphene nanosheets by the molten salt method.
[0025] In this embodiment, the graphene added to the metal matrix composite is surface modified, which improves the interface bonding ability between graphene and metal matrixes such as copper on the one hand, and suppresses the serious interface reaction between graphene and metal matrixes such as titanium on the other hand. W is selected as the surface modification element because it can be dissolved in most metals, which can ensure the interface bonding effect and not cause serious interface reaction with the metal matrix to generate brittle intermetallic compounds. At the same time, W atoms dissolved in the metal matrix are conducive to improving the high temperature performance of the matrix.
[0026] In this embodiment, the functional groups are introduced to change the graphene surface from being non-wetting to W element to being wetting, so that the reduced W element can nucleate and grow on the graphene surface, thereby achieving surface modification of the W element.
[0027] The molten salt system (NaCl-KCl) of this embodiment is in a molten state at high temperature. This liquid environment is WO 3 The molten salt can reduce the activation energy of the reaction and promote the conversion of W element from WO to graphene. 3 The W element is reduced in the particles and grows up by nucleation on the graphene surface, thereby forming a W element modified layer on the graphene surface. When the modified graphene is combined with a metal matrix, due to the presence of W simple substance on its surface, the direct contact of graphene with the metal matrix is avoided, and the graphene-metal matrix interface originally poorly combined is converted into two interfaces of graphene-W simple substance and W simple substance-metal matrix. Wherein, since the W simple substance grows up by nucleation in situ on the graphene surface, the interface between it and the graphene is well combined. At the same time, the W simple substance will diffuse into the metal matrix by solid solution, and it also has good interface combination. That is, by W surface modification, the graphene-metal matrix interface with poor interface combination or serious interface reaction is converted into a good combination, and there is no graphene-W simple substance-metal matrix interface with serious interface reaction, thereby effectively solving the problem of poor interface between graphene and matrix.
[0028] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the particle size of the graphene nanosheets in step 1 is 1-5 μm and the thickness is 5-20 nm. The rest is the same as specific embodiment 1.
[0029] Specific implementation method 3: This implementation method is different from specific implementation method 1 in that the volume concentration of the hydrofluoric acid solution in step 1 is 5-20%. Other aspects are the same as those of specific implementation method 1.
[0030] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that the ultrasonic dispersion time in step 1 is 30 to 60 minutes. The rest is the same as specific embodiment 1.
[0031] Specific embodiment 5: This embodiment differs from specific embodiment 1 in that the molar ratio of NaCl to KCl in step 2 is 1:(0.5-2). Other aspects are the same as those of specific embodiment 1.
[0032] Specific implementation method 6: This implementation method is different from the specific implementation method 1 in that: the WO 3 The particle size of the particles is 1-5 μm. Other aspects are the same as those of the first embodiment.
[0033] Specific implementation method 7: This implementation method is different from the specific implementation method 1 in that: the WO 3 The molar ratio of the particles to the graphene with surface functional groups is 1:(5-20). The rest is the same as the first embodiment.
[0034] Specific embodiment 8: This embodiment differs from specific embodiment 1 in that the volume ratio of the mixed powder to the mixed salt in step 3 is 1:(2-4). Other aspects are the same as those of specific embodiment 1.
[0035] Specific embodiment 9: This embodiment differs from specific embodiment 1 in that the reaction temperature in step 4 is 950-1100° C. and the holding time is 30-120 min. The rest is the same as specific embodiment 1.
[0036] Specific embodiment 10: This embodiment differs from the specific embodiment 1 in that the number of flushing times in step 5 is 3 to 5. The rest is the same as the specific embodiment 1.
[0037] The following examples are used to verify the beneficial effects of the present invention:
[0038] A method for preparing W surface-modified graphene nanosheets by a molten salt method is specifically carried out in the following steps:
[0039] 1. Graphene nanosheets with a particle size of 1 to 5 μm and a thickness of 5 to 20 nm are washed with distilled water and dried, and then ultrasonically dispersed in a hydrofluoric acid solution with a volume concentration of 10% for 30 minutes, so that the graphene is fully dispersed in the solution and fully contacted with HF to functionalize its surface. After the ultrasonic treatment, the graphene is washed with distilled water again and dried to obtain graphene with surface functionalization;
[0040] 2. Mechanically mix NaCl and KCl in a molar ratio of 1:1 to obtain a mixed salt;
[0041] 3. Add WO in a molar ratio of 1:8 3 The particles and the graphene with surface functional groups are mechanically mixed uniformly to obtain a mixed powder; the mixed powder is spread on the bottom of a crucible, and the surface of the mixed powder is covered with mixed salt to obtain a crucible containing the mixed salt and the mixed powder; the volume ratio of the mixed powder to the mixed salt is 1:2;
[0042] Fourth, the crucible containing the mixed salt and the mixed powder was placed in a heat treatment furnace at a reaction temperature of 1000°C and kept warm for 30 minutes in an argon atmosphere to modify the surface of graphene. 3 The particles react with graphene to reduce W single substance, which nucleates and grows on the graphene surface, thereby achieving W surface modification. After the reaction is completed, the crucible is cooled to below 100° C. in an argon atmosphere and the crucible is taken out.
[0043] 5. The reactants in the crucible are taken out, rinsed with distilled water and filtered with filter paper to completely remove the salt in the mixed powder, and the graphene surface modified by the W element is separated and dried, thus completing the preparation of the W element surface modified graphene nanosheets by the molten salt method.
[0044] The room temperature tensile properties of the hot-pressed sintered composite material prepared by W-modified graphene were tested, and the engineering stress-strain is shown in the figure. The tensile strength of the W-modified graphene-reinforced Ti-based composite material is close to 380MPa, which is about 20MPa higher than that of pure titanium, while still retaining a fracture strain of about 0.17. At the same time, when the graphene content is less than 0.5wt.%, the thermal conductivity exceeds 19W / (m·K), which is about 80% higher than that of pure titanium, proving that W-surface-modified graphene can improve the interface of the composite material, improve strength, and also have extremely high thermal conductivity improvement efficiency.
Claims
1. A method for preparing W surface-modified graphene nanosheets by a molten salt method, characterized in that The method for preparing W surface-modified graphene nanosheets by molten salt method is specifically carried out in the following steps:
1. The graphene nanosheets are washed with distilled water and dried, and then ultrasonically dispersed in a hydrofluoric acid solution to functionalize the graphene surface. After the ultrasonic dispersion is completed, the graphene nanosheets are washed with distilled water again and dried to obtain graphene with functionalized surface; 2. Mechanically mix NaCl and KCl to obtain mixed salt; 3. Mechanically mixing the WO3 particles and the surface functionalized graphene uniformly to obtain a mixed powder; spreading the mixed powder on the bottom of a crucible, and covering the surface of the mixed powder with mixed salt to obtain a crucible containing the mixed salt and the mixed powder; 4. Put the crucible containing the mixed salt and the mixed powder into a heat treatment furnace to perform surface modification of graphene under an argon atmosphere; after the reaction is completed, cool the furnace to below 100° C. under an argon atmosphere and take out the crucible; 5. The reactants in the crucible are taken out, rinsed with distilled water and filtered with filter paper, and the graphene surface modified by the W element is separated and dried, thereby completing the preparation of the W element surface modified graphene nanosheets by the molten salt method.
2. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The graphene nanosheets in step 1 have a particle size of 1 to 5 μm and a thickness of 5 to 20 nm.
3. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The volume concentration of the hydrofluoric acid solution in step 1 is 5-20%.
4. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The ultrasonic dispersion time in step 1 is 30 to 60 minutes.
5. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that In step 2, the molar ratio of NaCl to KCl is 1:(0.5-2).
6. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The particle size of the WO3 particles in step 3 is 1-5 μm.
7. The method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The molar ratio of the WO3 particles to the surface functionalized graphene in step 3 is 1:(5-20).
8. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that In step 3, the volume ratio of the mixed powder to the mixed salt is 1:(2-4).
9. A method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The reaction temperature in step 4 is 950-1100° C., and the insulation time is 30-120 min.
10. The method for preparing W surface-modified graphene nanosheets by a molten salt method according to claim 1, characterized in that The number of flushing times in step 5 is 3 to 5 times.
Citation Information
Patent Citations
Metal-matrix composite material and preparation method thereof
CN105861866A
Preparation method for aluminum-graphene metallic composite
CN106435244A
Novel graphene-covered titanate compound and preparation method thereof
CN106634056A
Preparation method of grapheme-tungsten carbide synergistic enhanced copper-based composite material
CN110453107A
A graphite sheet reinforced aluminum matrix composite material and its preparation method
CN114934221A